Through a Glass Darkly: The Social Sciences Look at the Neoliberal University - Thornton, Margaret (ANU Press, 2014)
This collection of essays arose from a workshop held in Canberra in 2013 under the auspices of the Academy of Social Sciences in Australia to consider the impact of the encroachment of the market on public universities.
English
Keywords: Universities; study; politics; social sciences; students; university; Australia; Higher education; Neoliberalism; Public university